Three dimensional kinematics of rapid compensatory eye movements in humans with unilateral vestibular deafferentation - Tian, Jun-Ru (2007)
Saccades executed with the head stationary have kinematics conforming to Listing's law (LL), confining the ocular rotational axis to Listing's plane (LP). In unilateral vestibular deafferentation (UVD), the vestibuloocular reflex (VOR), which does not obey LL, has at high head acceleration a slow phase that has severely reduced velocity during ipsilesional rotation, and mildly reduced velocity during contralesional rotation. Studying four subjects with chronic UVD using 3D magnetic search coils, we investigated kinematics of stereotypic rapid eye movements that supplement the impaired VOR. We defined LP with the head immobile, and expressed eye and head movements as quaternions in LP coordinates. Subjects underwent transient whole body yaw at peak acceleration 2,800°/s(2) while fixating targets centered, or 20° up or down prior to rotation. The VOR shifted ocular torsion out of LP. Vestibular catch-up saccades (VCUS) occurred with mean latency 90 ± 44 ms (SD) from ipsilesional rotation onset, maintained initial non-LL torsion so that their quaternion trajectories paralleled LP, and had velocity axes changing by half of eye position. During contralesional rotation, rapid eye movements occurred at mean latency 135 ± 36 ms that were associated with abrupt decelerations (ADs) of the horizontal slow phase correcting 3D deviations in its velocity axis, with quaternion trajectories not paralleling LP. Rapid eye movements compensating for UVD have two distinct kinematics. VCUS have velocity axis dependence on eye position consistent with LL, so are probably programmed in 2D by neural circuits subserving visual saccades. ADs have kinematics that neither conform to LL nor match the VOR axis, but appear instead programmed in 3D to correct VOR axis errors.